The aesthetics of narrative in the collection of Ankawi short stories of the storyteller Noori Boutros - JAWAD, SIHAM .H. (Utopía y Praxis Latinoamericana, 2021)
ABSTRACT The narrative that operates in the stories of Noori Boutros are two different spaces, one heading towards objective narratives, the other in the narrative of self-narration, and a third space that does not lean on certain grounds. This rotation between consciences in the narrative work is a necessity aesthetic so that the narrative process does not stay in the same pattern, the beauty of the narrative work lies in its diversity and difference. The storyteller and through what we have investigated in the collection of short stories, we find it did not stop at a narrative level, but in the multiplicity of several ones. RESUMEN La narrativa que opera en los relatos de Noori Boutros son dos espacios diferenciados, uno orientado hacia narrativas objetivas, el otro en la narrativa de la auto-narración, y un tercer espacio que no se apoya en ciertos fundamentos. Esta rotación entre conciencias en el trabajo narrativo es una necesidad estética, para que el proceso no se quede en el mismo patrón, la belleza del trabajo narrativo radica en su diversidad y diferencia. El narrador a través de lo que hemos investigado en recopilación de relatos cortos, encontramos que no se detuvo en el nivel narrativo, sino en la multiplicidad de varios niveles.